An exploration of the socio-cultural factors influencing condom use intentions and behaviours of migrant youth in South Africa - Titus, Raylene Rozita (Department of Social Development, 2017)
Migrant health has become a critical issue in current HIV intervention discourses as this particular cohort has an increased vulnerability to HIV infection. The purpose of this study is to explore socio-cultural determinants influencing condom use intentions and behaviour of young migrant youth residing in Cape Town South Africa. This qualitative study employed purposive and snowballing sampling techniques to explore with migrant youth their intentions and behaviour towards condoms use within their socio-cultural contexts. The interviews were in-depth open ended questions and conducted in English. The sample were drawn from 20 single respondents from Sub-Saharan Africa, notably from Zimbabwe, Nigeria, Congo, Cameroon, Kenya and Malawi. The mean age was 23 years with a range of 20 years to 25 years, the gender distribution was even with 10 males and 10 females. The research findings indicate that young migrants have a good understanding of the functions of condoms and the positive preventative tool it is for pregnancy prevention and sexually transmitted disease prevention. However the use of condoms, even when freely available, is a contested issue as socio cultural influences have an impact on the intentions and behaviour towards condom use among young migrant youth. Findings indicated that traditional norms on sexual behaviour prohibits young migrants to freely discuss safer sexual options and methods of safer contraceptive choices. Traditional gendered norms in sexual relationships and gendered expectations of condom use are current issues that migrant youth are grappling with. The nexus between socio-cultural norms and safer sexual choices such as condoms use places young migrants' at-risk cohort as they are currently outside of the realms of socio-cultural contexts, with higher education expectations and delay of marriage customs. As the results cannot be generalised to the entire migrant youth population due to the small sample size of only 20 young migrants' narratives, the need for further research on a larger sample might provide more insight into current realities of transitioning young migrants who lives outside of the boundaries of current socio-cultural paradigms.